الاستعارة في آيات يوم القيامة بين الإفراد والتركيب (Journal of Hama University, 2025)
Metaphor is a clear rhetorical phenomenon in the verses of Doomesday as well as  it is a means of language since it has autosuggestions that work to link the unknown thing with the known thing, to report new facts, and adduct the unssen world to the recipient and imagine the events in it, leading to an emotional and mental impact on                                    the recipient.                                                                                                                            Hence, this research seeks to shed light on the metaphor in the verses of Doomesday with its various types; verbal and nominal, single and compound, within the contexts of resurrection, gathering, heaven, and hell, and to reveal the aesthetics of metaphor,                                   purpose for which metaphor was employed in the context.                             the and    The research was concluded with results that showed the dominance of the single metaphor over the compound, and the diversity of metaphor structures between verbal and nominal in a way that serves the context, the function of the metaphor, and its effectiveness in influencing the recipient by using his mind to analyze and comprehend it .